CREPT is required for murine stem cell maintenance during intestinal regeneration - Liu Yang; Haiyan Yang; Yunxiang Chu; Yunhao Song; Lidan Ding; Bingtao Zhu; Wanli Zhai; Xuning Wang; Yanshen Kuang; Fangli Ren; Baoqing Jia; Wei Wu; et al. (Nature Communications, 2021)
The role of CREPT, a recently identified tumor-promoting gene, outside of tumors is unclear. Here, the authors identify CREPT as maintaining murine intestinal stem cells, with embryonic deletion causing impaired cell proliferation and regeneration.